2003
DOI: 10.1016/s0924-0136(03)00806-9
|View full text |Cite
|
Sign up to set email alerts
|

Tensile properties and fracture locations of friction-stir-welded joints of 2017-T351 aluminum alloy

Abstract: Friction stir welding (FSW) is a new and promising welding process that can produce low-cost and high-quality joints of heat-treatable aluminum alloys because it does not need consumable filler materials and can eliminate some welding defects such as crack and porosity. In order to demonstrate the friction stir weldability of the 2017-T351 aluminum alloy and determine optimum welding parameters, the relations between welding parameters and tensile properties of the joints have been studied in this paper. The e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
227
0
4

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 442 publications
(245 citation statements)
references
References 12 publications
14
227
0
4
Order By: Relevance
“…Microhardness measurements on the joint cross-section both of the as-welded and post-weld aged joints shows the typical hardness distribution of a heat treatable aluminum alloy after FSW 9,17 . The observed data dispersion agrees with what has been previously recorded in literature 5,10 .…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Microhardness measurements on the joint cross-section both of the as-welded and post-weld aged joints shows the typical hardness distribution of a heat treatable aluminum alloy after FSW 9,17 . The observed data dispersion agrees with what has been previously recorded in literature 5,10 .…”
Section: Discussionmentioning
confidence: 93%
“…So far, many studies have been carried out on FSWed joints after a heat treatment to assess the properties of the weld structure. In particular, in the 2xxx-series, the following alloys were friction stir welded to compare the mechanical properties of the joints in as-welded and postweld aged condition: 2219-O 15 , 2219-T87 16 , 2017-T351 17 , and 2024-T4 18 . It was found that the post-weld aged 2219-T87 FSWed joints showed superior fatigue performance compared to electron beam and gas tungsten arc welded joints.…”
Section: Introductionmentioning
confidence: 99%
“…This should be attributed to the fact that the 10-joint has a large softening region width. During tensile test, the plastic deformation is primarily concentrated in the softening region [19,20]. Larger amount of grains of 10-joint are able to be involved in the plastic deformation during tensile test, which retards the occurrence of work hardening and thus leads to the good ductility.…”
Section: Joint Mechanical Behaviormentioning
confidence: 99%
“…Artificial aging was carried out at 165 °C for a soaking time of 18 h. The quenched joints were heated in the furnace from room temperature to 165 °C at a rate of 10 °C/min. After the soaking time, ©IJRASET (UGC Approved Journal): All Rights are Reserved the joints were slowly cooled in the furnace to room temperature and the whole PWHT process was completed [10]. PWHT of the prepared specimen was performed at chemical technology lab in SLIET, Longowal.…”
Section: B Post Weld Heat Treatmentmentioning
confidence: 99%